(untitled) (Jurnal Pembangunan Sosial, 2013)
Rural traditional community is declining all over the world. After the New Economic Policy was launched, the urbanization of Malaysia has become accelerated and as a consequence more and more people living in urban areas. Thus, the life style of the rural folk has changed. The social solidarity which is very sinonim to the rural folks has also been changing. Urban community is said to be anonymous. This paper examines whether the urbanization process that has taken place in rural areas affects the characteristics and culture of the rural folks. To meet this objective, 240 older persons aged 60 years and above in the district of Limbongan, Pasir Putih, Kelantan has been selected as samples of the survey. Based on face-to-face interviews conducted in this rural Kelantan, it was revealed that the majority of older persons reported they are always interacting with their neighbours. They are also fond of each other, have mutual trust, may receive criticism and have mutual respect between each other. The quality of social interactions, one more aspect of social solidarity, of older person and their neighbours, was also not changing. However, to prevent the weakening of social solidarity of the rural folks in the future, this article suggests that the we feelings among the youth in rural community should be inculcated as early as possible in their lives.